Current options for cannabinoids in the treatment of Parkinson’s disease - Zdzieblo, Piotr; Machała-Ćwikła, Ewelina; Łapińska, Urszula; Ćwikła, Piotr; Machała, Kamila; Zdziebło, Anna; Machała, Dominika; Zdzieblo, Katarzyna; Bieniasz, Anna (Quality in Sport, 2024)
The utility of cannabinoids as agents used to treat diseases is a popular topic of discussion these days. The approval of medical marijuana continues to stir up controversy. As far back as ancient times, hemp was used for medicinal purposes. These plants have the ability to produce phytochemicals and other compounds such as flavonoids and terpenes. Respective species of hemp differ in the content of particular chemical compounds and therefore have different possible uses. Among the best-known phytocannabinoids found in hemp are delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD). They have partially opposing effects and interact with the corresponding receptors of the endocannabinoid system in the body’s tissues. We also distinguish between cannabinoids of endogenous origin - endocannabinoids (EC) and synthetic cannabinoids (SC). The effects of THC and CBD on the human body are still being studied. Information about them that appears in the media, is often reported inaccurately or incompletely. There is now a growing body of research into the use of cannabinoids to treat and alleviate the symptoms of many diseases. Due to the neuroprotective effects of THC and CBD, researchers’ work has focused on using them to treat neurodegenerative diseases, which include Parkinson’s disease (PD).